FACTORS AFFECTING ENTERPRISE RESOURCE PLANNING ADOPTION ON FIRMS’ PERFORMANCE AMONG MEDIUM-SIZED ENTERPRISES. - Yusuff, Adejare Aremu; Shahzad, Arfan; Hassan, Shahizan (International Journal of Supply Chain Management, 2019)
Empirical evidence suggests that the adoption of ERP facilitates organizational processes and activities including sales, billing, marketing, human resource management, quality control and production, which in turns, could ensure general performance. This study proposes a theoretical framework that identified factors that affecting ERP system adoption among medium-sized enterprise firms, such as organizational culture, technology infrastructures support / quality of internet and top management support. The present study also applied resource based value and contingency theories to explain the factors that affect ERP system adoption. In this study, the proposed theoretical framework has been formulated based on data obtained from a newly developed questionnaire. The sets of questionnaire were distributed to one hundred and four (104) medium-sized enterprises firms in Ogun State, Nigeria. CEO / director and managers were selected as the key respondents of the questionnaire. The empirical data were analyzed using the Partial Least Squares Structural Equation Modelling. The result obtained revealed that both organizational culture and top management support significantly influence the adoption of the ERP system to improve the performance of medium-sized enterprises firms. In this regard, technology infrastructure support has no significant relationship with ERP system adoption. The outcomes of this study are useful for firms adapting ERP as they would be able to strategize future ERP system implementation in different sectors, such as education, and large firms in general. One limitation of the study is its small sample size. Moreover, the author has not included other measures of medium sized enterprises performance outside of the procurement area despite these factors could provide further insights to medium sized enterprises performance, and will be an interesting topic for future research.